2017
DOI: 10.12659/msm.903427
|View full text |Cite
|
Sign up to set email alerts
|

Leptocarpin Suppresses Proliferation, Migration, and Invasion of Human Osteosarcoma by Targeting Type-1 Insulin-Like Growth Factor Receptor (IGF-1R)

Abstract: BackgroundLeptocarpin (LTC) has drawn much attention for suppressing tumor growth or reducing inflammation. However, the effect of LTC on osteosarcoma has rarely been reported. Our object was to determine whether LTC suppresses MG63 cell proliferation, migration, and invasion, and whether type-1 insulin-like growth factor receptor (IGF-1R) is one of the targets in LTC suppressing osteosarcoma.Material/MethodsCytotoxicity of LTC was performed by use of a cell-counting kit-8 (CCK-8). RNA interference (RNAi) or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…For cancer cells, negative absorbance values were measured, suggesting that a lethal level of LTC was reached, whereas for CoN cells and at the same LTC concentration only a decrease in their metabolic activity was observed. This result is in line with previous studies that have shown that LTC acts specifically on tumor cells of different origin [8,10,11]. Finally, treatment with the extract of clonal explants (T2, 12 ppm) induced a decrease in metabolism in both cell lines but without reaching lethal levels.…”
Section: Asseessment Of Biological Activity Of In Vitro Plant Extractssupporting
confidence: 91%
See 1 more Smart Citation
“…For cancer cells, negative absorbance values were measured, suggesting that a lethal level of LTC was reached, whereas for CoN cells and at the same LTC concentration only a decrease in their metabolic activity was observed. This result is in line with previous studies that have shown that LTC acts specifically on tumor cells of different origin [8,10,11]. Finally, treatment with the extract of clonal explants (T2, 12 ppm) induced a decrease in metabolism in both cell lines but without reaching lethal levels.…”
Section: Asseessment Of Biological Activity Of In Vitro Plant Extractssupporting
confidence: 91%
“…Previous phytochemical studies of L. rivularis have shown that extracts obtained from leaves, bark, and flowers exhibit antioxidant, hypoglycemic, and anticancer effects [3][4][5][6][7]. These biological activities have been attributed to the presence of sesquiterpene lactones, i.e., leptocarpine (LTC) as the major component and small amounts of rivularin and the 17,18-dihydroleptocarpin derivative [8][9][10][11]. It has also been described that LTC presents important cytotoxic effects on several cancer cell lines by inducing apoptosis [10], and inhibitory activity on specific growth factors in osteosarcoma [11].…”
Section: Introductionmentioning
confidence: 99%
“…Both IR and IGF-1R have been investigated as therapeutic targets. A number of preclinical in vitro studies using OS cell lines have successfully suppressed cell proliferation, migration and invasion by inhibiting the IR/IGF-1R signaling pathway using miRNA, siRNA, and inhibitory antibodies [18,[21][22][23][24][25]. Kolb et al used R1507, an anti-IGF-1R antibody, in OS xenograft tumor models to delay tumor growth in 4 of 6 OS xenografts with significant improvement in EFS [26].…”
Section: Discussionmentioning
confidence: 99%